HIV anti-stigma toolkit for educators (CARICOM Secretariat GeorgetownGY, 2009)
Aims to assist managers and key decision-makers within the education sector as well as members of teaching and administration staff within educational institutions to recognise HIV-related stigma and discrimination in the school setting and to be equipped to challenge and reduce these incidents.\n
Keywords: HIV